Asset Management in Islamic Inheritance: A Solution for Economic Empowerment Obstacles - Indah Puspitasari; Amin Wahyudi (Islamic Economics Journal, 2024)
If inheritance assets are transferred, the economic well-being of heirs should increase. However, conflicts among heirs often prevent this, resulting in unproductive or disputed assets with unclear ownership. These disputes significantly hinder the economic progress of the heirs. This article attempts to propose a solution to the problem. According to Islamic inheritance principle, before distribution, there are three obligations must be fulfilled: handling the body's costs, repaying the deceased's debts, and executing their will within limits. Afterward, remaining assets can be distributed among entitled heirs according to Islamic inheritance laws. The remaining assets, termed inheritance, can enhance heirs economic empowerment when distributed. The asset management approach that focuses on Islamic inheritance is expected to further impetus for the economic strengthening of individual beneficiaries specifically, as well as benefit the Muslim community and the general public in the country, such as alleviating conflicts and cultivating heightened economic activity. This qualitative study utilizes a library research approach with phenomenological lens. Based on the literature review conducted, asset management based on the principles of  Islamic heritage with the aim of increasing economic empowerment is: providing education to families about Islamic inheritance; accurately record ownership of property, debts, and receivables; the written documents as proof of ownership of asset, and the determination of inheritance rights and their division should be held; utilizing inheritance assets productively to establish sustainable individual or family finances.